Unfractionated Heparin versus Low Molecular Weight Heparin for Venous Thromboembolism Prophylaxis in Acutely Ill Medical Patients: A Meta-analysis - Rendi Dwi Prasetyo; Rudy Afriant (HM Publisher, 2025)
Background: Venous thromboembolism (VTE) is a significant cause of morbidity and mortality in acutely ill medical patients. Both unfractionated heparin (UFH) and low molecular weight heparin (LMWH) are effective for VTE prophylaxis, but their relative efficacy and safety remain unclear. Methods: We conducted a meta-analysis of randomized controlled trials (RCTs) comparing UFH and LMWH for VTE prophylaxis in acutely ill medical patients. We searched MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials from 2013 to 2024. The primary outcome was the incidence of VTE. Secondary outcomes included major bleeding and mortality. Results: Seven RCTs with a total of 5,412 patients were included. LMWH was associated with a significantly lower risk of VTE compared to UFH (relative risk [RR] 0.68; 95% confidence interval [CI] 0.52-0.88; p = 0.004). There was no significant difference in major bleeding (RR 0.91; 95% CI 0.65-1.27; p = 0.58) or mortality (RR 0.93; 95% CI 0.78-1.11; p = 0.43) between the two groups. Conclusion: LMWH is more effective than UFH for VTE prophylaxis in acutely ill medical patients without increasing the risk of major bleeding or mortality. LMWH should be considered the preferred agent for VTE prophylaxis in this population.